2020
DOI: 10.3389/fpsyt.2020.480671
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Yale Food Addiction Scale 2.0: Validation Among Non-Clinical and Clinical French-Speaking Samples and Comparison With the Full Yale Food Addiction Scale 2.0

Abstract: Objectives: The modified Yale Food Addiction Scale 2.0 (mYFAS 2.0) was designed to assess food addiction using a shorter version than the YFAS 2.0. We lack data about the psychometric properties of the mYFAS 2.0 in patients with obesity, as well as studies comparing the psychometric properties of the mYFAS 2.0 versus the full YFAS 2.0. This study aimed to validate the French-language mYFAS 2.0 in a non-clinical population (study 1, n = 250), to determine the yet unknown psychometric properties of this scale in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…The construct validity of the mYFAS 2.0 has been confirmed in prior research and has supported the 11-factor structure of the mYFAS 2.0 (18). Moreover, the association between the mYFAS 2.0 and its original version (i.e., YFAS 2.0) has been found to be satisfactory (18,19). As far as the present authors' are aware, the mYFAS 2.0 has been psychometrically evaluated in eight previous studies.…”
Section: Introductionsupporting
confidence: 74%
“…The construct validity of the mYFAS 2.0 has been confirmed in prior research and has supported the 11-factor structure of the mYFAS 2.0 (18). Moreover, the association between the mYFAS 2.0 and its original version (i.e., YFAS 2.0) has been found to be satisfactory (18,19). As far as the present authors' are aware, the mYFAS 2.0 has been psychometrically evaluated in eight previous studies.…”
Section: Introductionsupporting
confidence: 74%
“…The one-factor structure that has been previously found in multiple validation papers (German [37], Turkish [40], French [39], Czech [41], and Italian [38]), was confirmed in our sample. In terms of reliability, the Cronbach's alpha value obtained in the present study (0.859) was higher than the one found in the Turkish (0.70) [40], German (0.82) [37], and French (0.79) [39] versions, but a little lower than the one found in the Czech version (0.89) [41].…”
Section: Discussionsupporting
confidence: 86%
“…The one-factor structure that has been previously found in multiple validation papers (German [37], Turkish [40], French [39], Czech [41], and Italian [38]), was confirmed in our sample. In terms of reliability, the Cronbach's alpha value obtained in the present study (0.859) was higher than the one found in the Turkish (0.70) [40], German (0.82) [37], and French (0.79) [39] versions, but a little lower than the one found in the Czech version (0.89) [41]. In addition, mYAS-AR-Leb score was significantly and strongly associated with higher mental health issues in the present study; these findings corroborate the ones found in a meta-analysis [17], which showed that there is a connection between some criteria of mental illness and those of food addiction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The model contains more quantitative information and a continuous scale of measurement compared to a CTT approach and assumes that each individual has a fixed latent tendency along with each item with a particular fixed difficulty [25]. The Rasch model also will help assess the unidimensionality of both the YFAS 2.0 and mYFAS 2.0, and both instruments have been found to be unidimensional [20,[26][27][28][29][30][31][32][33][34][35][36][37][38]. Moreover, both the YFAS 2.0 and mYFAS 2.0 were expected to create a single factor structure of FA to differentiate between those with or without FA [18,19].…”
Section: Introductionmentioning
confidence: 99%